Potentiodynamic Polarization Study of PH3 Electrochemical Oxidation - Ainur Tukibayeva; Abduali Bayeshov; Dina Asylbekova; Laura Aikozova; Aizhan Essentayeva (Electrochemical Science Advances)
ABSTRACT In this study, the electrochemical behaviour of phosphine in sulphuric acid solutions on the surface of various electrode materials was conducted by voltammetric investigations. The effects of electrode materials such as lead, copper, and platinum electrodes on the PH3 anodic oxidation were investigated. Polarization curves were recorded by saturating the sulphuric acid solution with phosphine. The results received show that the electrochemical oxidation of phosphine on the lead electrode is accompanied by an oxygen evolution potential and, on the copper electrode, copper (II) ions show catalytic effects. The maximum anodic oxidation of phosphine on a platinum electrode was observed at the potential range of 0.8–1.0 V, and in the presence of copper (II) ions on the polarogram a maximum of phosphine oxidation is recorded at a potential of approximately 0.1–0.2 V.